The Speading Pattern of Ambilateral, Cogged Belted Plot Fertilizer Distributors - Hagymássy, Zoltán (Acta Agraria Debreceniensis, 2003)
The mechanization of fertilizer distribution in the case of different types of fertilizers often poses problems. As a result, I have designed and constructed a brand new type of plot fertilizer distributor. This machine of moderate price can be controlled easily; it provides accurate distribution and versatility. The main part of this machine is an ambilateral cogged belt. I briefly present the operation and the advantages of cogged belts. I investigated the spreading patterns at the front and the end part of the experimental plot. I demonstrate a method never seen so far in the investigation of spreading patterns. My method also shows marginal divergences and flat wedge effects in spreading patterns.